"All the real Indians died off" : and 20 other myths about Native Americans - Dunbar-Ortiz, Roxanne, 1938-; Gilio-Whitaker, Dina (Beacon Press, 2016)
"In this enlightening book, scholars and activists Roxanne Dunbar-Ortiz and Dina Gilio-Whitaker tackle a wide range of myths about Native American culture and history that have misinformed generations. Tracing how these ideas evolved, and drawing from history, the authors disrupt long-held and enduring myths such as: 'Columbus Discovered America'; 'Thanksgiving Proves the Indians Welcomed Pilgrims'; 'Indians Were Savage and Warlike'; 'Europeans Brought Civilization to Backward Indians'; 'The United States Did Not Have a Policy of Genocide'; 'Sports Mascots Honor Native Americans'; 'Most Indians Are on Government Welfare'; 'Indian Casinos Make Them All Rich'; [and] 'Indians Are Naturally Predisposed to Alcohol.' Each chapter deftly shows how these myths are rooted in the fears and prejudice of European settlers and in the larger political agendas of a settler state aimed at acquiring Indigenous land and tied to narratives of erasure and disappearance. Accessibly written and revelatory, "All the Real Indians Died Off" challenges readers to rethink what they have been taught about Native Americans and history."--Publisher's description.